RNase H1 Cooperates with DNA Gyrases to Restrict R-Loops and Maintain Genome Integrity in Arabidopsis Chloroplasts. Issue 10 (22nd September 2017) - Yang, Zhuo; Hou, Quancan; Cheng, Lingling; Xu, Wei; Hong, Yantao; Li, Shuai; Sun, Qianwen
Abstract : R-loop homeostasis in Arabidopsis plastid determines chloroplast genome stability and development. Abstract: Maintaining organellar genome integrity is essential for eukaryotic cells, and many factors can threaten genome integrity. R-loops are DNA:RNA duplexes produced during transcription, with the nontemplated DNA forming a single-stranded region. R-loops function in the regulation of transcription, DNA replication, and DNA repair, but can also be susceptible to lesions that form double-stranded breaks and thus induce genome instability. From investigating the function of a plant chloroplast-localized R-loop removing enzyme AtRNH1C, we have found that it is responsible for plastid R-loop homeostasis, chloroplast genome instability, and development. Interactome analysis revealed that AtRNH1C associates with multiple chloroplast-localized DNA and RNA metabolism-related proteins, including the core DNA gyrases complex. The interaction between AtRNH1C and AtGyrases was critical for R-loop homeostasis in chloroplast and important to release the transcription-replication conflicts in the highly transcribed and replication originated cp-rDNA regions and thus to reduce the DNA damage. Our results reveal the plastid R-loop accumulation leads to chloroplast DNA instability and provide insight into the maintenance of genome integrity in chloroplasts, in which the evolutionarily conserved RNase H1 and DNA gyrase proteins are involved.